Transcription of unrearranged antigen receptor genes in scid mice. - Schuler, W (1988)
The scid mouse mutant is severely deficient in lymphocytes; cells of the B or T lymphocyte lineage cannot be detected by either serological or functional assays. However, as shown here, germ-line transcripts of B cell immunoglobulin (Ig) constant and variable region genes and of T cell receptor (TCR) genes are detectable in lymphopoietic tissues of scid mice, as well as B and T lineage-specific lambda 5 and T3 delta transcripts. We conclude that B and T lineage-committed cells do arise in scid mice and that their Ig and TCR genes are accessible to enzymes involved in their recombination. This suggests that scid impairs lymphopoiesis at the stage at which antigen receptor genes normally undergo rearrangement.